Kesepadanan Terjemahan Polisemi: Penelitian Analisis Konten pada Terjemahan Surat al-Baqarah Kementerian Agama - Fariz Alnizar (Hayula: Indonesian Journal of Multidisciplinary Islamic Studies, 2017)
This research aims to assess the equivalence of polysemy translation from Arabic into Indonesian in al-Baqarah from the Indonesian Ministry of Religious Affairs translation version. The research was conducted from the results of al-Baqa>rah translation which is published by Ministry of Religious Affairs. This Reseach uses qulaitative method with content analysis. Primary data are derived from translation texts which is containing polysemy in the al-Baqa>rah translation of the ministry of religious affairs version, especially the result of translation toward verses which is containing polycemy. Secondary data are obtained from an authoritative interpretation books such as Tafsir Jami‘ al-Bayan, Tafsir al-Fahru al-Razi, Tafsir al-Ruh al-Ma‘ani and Tafsir al-Maraghi. The researche found that (1) there are 12 words of polycemy in Al-Baqarah which consisted of fi’il (verba), isim (nomina) and huruf (particles). (2). There are four procedures in the translations which are conducted by ministry of religious affairs such as transposition, modulation, subastraction and addition (3) the translations of polysemy in the al-Baqarah from ministry of religious affairs version have the type of equivalent translation, but the problem is there is the tendency of translators who often chose the prototypical meaning as option whereas there are words which should not be right if using that meaning and must refer to the secondary meaning.